HUBUNGAN ANTARA KUALITAS AIR DENGAN KEBIASAAN MAKANAN IKAN BATAK (Neolissochilus sumatranus) DI SUNGAI ASAHAN, SUMATERA UTARA - Mesrawati Purba; Ternala Alexander Barus; Syafruddin Ilyas (JBIO: jurnal biosains (the journal of biosciences), 2013)
The study of the water quality relationship and food habits of batak fish (Neolissochilus sumatranus) in Asahan river, North Sumatra was conducted. Aims of this research are to undesrtand the food habits of batak fish , the water quality of Asahan river and relationship between water quality and food habits of batak fish. Fish samples were caught by electrofishing and casnet and stomach content was analysis using volumetric method. Results showed that the batak fish  have allometric growth patten. Based on the data of stomach content shown that 38 organism, the major food of batak fish  based on index preponderance are Cymbella (42,56%), Navicula (56,90%) and Nitschia (47,09 %). Cymbella positively correlated with light penetration, light intensity, DO and BOD5 and negatively correlated with temperature,water current, pH, NO3 and PO4. Navicula positively correlated with water current, pH, DO, BOD5, NO3 and PO4 and negatively correlated with temperature, light penetration and light intensity. Nitzschia positively correlated with light intensity,   temperature, light penetration, pH and PO4 and negatively correlated with water current, DO, BOD5 and NO3. Indicating the condition of Asahan river is relatively in good condition and support fish growth as well